Rethinking humanitarian intervention in the 21st century - Warren, Aiden; Grenfell, Damian (Edinburgh Edinburgh University Press, 2017)
Since the Cold War, humanitarian interventions have transitioned through a range of stages. These 12 essays focus on the challenges associated with interventions, conflict and attendant human rights violations, unmitigated and systematic violence, state re-building, and issues associated with human mobility and dislocation. Each chapter is linked to the rest through three defining themes that permeate the book: the 'global and the local' in the context of interventions; extending and broadening the definitions associated with interventions; and mapping the evolution of interventions over the last three decades.
Introduction / Aiden Warren and Damian Grenfell. Part 1. The evolution of humanitarian interventions in a global era : Rethinking humanitarian-military interventions: violence and modernity in an age of globalisation / Damian Grenfell -- Peace in the twenty-first century: states, capital and institutions / Oliver P. Richmond -- The evolution of economic interventions and the violence of international accountability over the longue durée / Bronwen Everill -- Changing patterns of social connection across interventions: unravelling aberrant globalisation / Paul Battersby. Part 2. The limits of sovereignty and the ethics of interventions : A framework for reimagining order and justice: transitions in violence and interventions in a global era / Michaelene Cox -- Humanitarian intervention? Responding ethically to globalising violence in an age of mediated violence / Paul James -- "Manifestly failing" and "unwilling or unable" as intervention formulas: a critical assessment / Ingvild Bode -- Interventions and the limits of the responsibility to protect: regional organisations and the global south / Joseph Hongoh -- Regulating the abstraction of violence: interventions and the deployment of new technologies globally / Aiden Warren. Part 3 The politics of post-intervention (re-)building and humanitarian engagement : (Re-)building the world: local agency and human security in the new millennium / Trudy Fraser -- Who rebuilds? Local roles in rebuilding shattered societies / Susan H. Allen -- Transforming the discourse of civil-military interaction in humanitarian environments / Vandra Harris. Index.
Includes bibliographical references and index.
Keywords: Humanitarian intervention; Humanitarian intervention -- Political aspects; Intervention (International law)